SAINT-SABBAISM AND MEDIALA: A PARADIGM OF THE ART MOVEMENT (Heritage, 2024)
Mediala is the art community whose members have been: Olga Ivanjicki, Leonid Šejka, Milić Stanković of Mačva, Uroš Tošković, Vladimir Veličković, Ljubomir Popović, Kosta Bradić, Vladan Radovanović, Siniša Vuković, Miro Glavurtić, Svetozar Samurović, Milovan Vidak, Miodrag Đurić, Predrag Ristić and others. The art of Mediala is considered in the light of a tradition that should elucidate its complexity and universality. It concerns the Orthodox Christianity, whose cosmology is presented through the iconography of Byzantine style. In that respect, Mediala is an extension of the Russian avant-garde which was also based upon cosmology of the icon. An immediate continuation is the integral painting by Leonid Šejka, whose mystical verticalism is considered to be a paradigm of Mediala.The architecture of Predrag Ristić has elucidated Mediala in terms of the continuum and the hesychastic theology. He has recognized it through the Saint-Sabbaist institution of the patron saint which is a testimony of the eternal truth. Mediala is therefore significant for conceptualization of Saint-Sabbaism which is established during the XX century.
Keywords: integral painting, perspective, iconography, cosmology, hesychasm, continuum, Rus- sian avant-garde